Quality Assurance of Different Types of Yoghurt in Khartoum State Markets - Elfaki, Ahmed E.; Abd Elrazig, Ebtihag B. (Gezira Journal of Engineering and Applied Sciences, 2010)
This study was carried out to insure the quality of different types of yoghurt in Khartoum State produce by Sudanese yoghurt producing companies (Capo, Daima, Kenana) and Traditional yoghurt. Chemical and microbial examinations were conducted for the products and during ten days storage period. Capo, Daima and Kenana yoghurts showed significant differences (p≤0.05) in protein content while there was no significant difference between Capo and traditional yoghurts. Ash and fat contents were of insignificant differences in all samples. The titratable acidity (as lactic acid) showed insignificant differences in all samples as well.  pH  values almost the same . The minerals content (mg /100g) for: calcium ranged from 680 to 663; phosphate (90 to77); sodium ( 80 to 73) potassium ( 123 to 103) ; iron ( 50 to 37) and magnesium ( 13 to1.9). The total amino acids (mg/100gm ) were 2042.857, 1862.225, 2330.725 and 1883.1 for Capo, Daima, Kenana and traditional yoghurt, respectively. Total bacterial viable count (cfu/ml) of Kenana yoghurt recorded the highest level (4.8x10 7 ) while the traditional possessed the less (7.3x10 6 ). Lactobacillus was higher in Kenana (9.8x10 6 ) and less in the Traditional (8.7x10 5 ).   Streptococcus was higher in Capo (6.0x10 6 ) and lower in the traditional (3.2x10 4 ). Coliforms were recorded in the traditional (not E.coli ).The traditional yoghurt obtained 5.6×10 5 /cf mg as yeasts while the other samples obtained no yeasts.